Pengaruh Pendidikan Kewirausahaan dan Efikasi Diri Terhadap Minat Berwirausaha Siswa SMK di Kota Semarang - Tri Adhi Santoso; Aulia Vidya Almadana (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
This study aims to determine the entrepreneurial intentions of vocational school students in Semarang City. The factors used to explain entrepreneurial intentions are entrepreneurship education and self-efficacy. This research was conducted in the city of Semarang. The number of samples used was 100 respondents using probability sampling techniques. The data that has been collected is processed using multiple regression analysis techniques. The data sources used are primary data and secondary data. The results showed that the two independent variables (Entrepreneurship Education and Self Efficacy) had a positive and significant effect on entrepreneurial intentions of vocational school students in Semarang City